2009
DOI: 10.1128/jb.01721-08
|View full text |Cite
|
Sign up to set email alerts
|

Rrp2, a σ 54 -Dependent Transcriptional Activator of Borrelia burgdorferi , Activates rpoS in an Enhancer-Independent Manner

Abstract: Rrp2 is the sole 54 -dependent transcriptional activator present in the Borrelia burgdorferi genome. We showed that recombinant Rrp2 binds to DNA in a sequence-nonspecific manner. During infection, Rrp2 activates 54 -dependent rpoS expression without an apparent upstream enhancer element commonly associated with other 54 -dependent transcriptional activators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 27 publications
5
77
0
Order By: Relevance
“…5c), suggesting that the decrease of RpoS in the csrA Bb mutant occurs upstream of the RpoS pathway. The expression of rpoS is directly controlled by the alternative sigma factor RpoN, whose expression requires the activation of the response regulator Rrp2 (9,55). In addition, recent studies showed that BosR, a homolog of the Fur regulatory protein, interfaces with the Rrp2-RpoN-RpoS network (24,38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5c), suggesting that the decrease of RpoS in the csrA Bb mutant occurs upstream of the RpoS pathway. The expression of rpoS is directly controlled by the alternative sigma factor RpoN, whose expression requires the activation of the response regulator Rrp2 (9,55). In addition, recent studies showed that BosR, a homolog of the Fur regulatory protein, interfaces with the Rrp2-RpoN-RpoS network (24,38).…”
Section: Resultsmentioning
confidence: 99%
“…Rrp2-RpoNRpoS forms a central regulatory network of B. burgdorferi (11,23,66). RpoN directly controls the expression of RpoS, and Rrp2 is an activator of the RpoN-RpoS pathway (9,66). In addition, recent studies showed that BosR, a homolog of the Fur regulatory protein, interfaces with the Rrp2-RpoN-RpoS network (24,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signals contained within the nymphal blood meal trigger a complex series of transcriptional, antigenic, and physiological changes that enable spirochetes colonizing the midgut to disseminate through tick tissues while preparing for growth within the mammalian host (11,15,16,67); the Rrp2/RpoN/RpoS regulatory pathway is central to this transmission-associated program (6,7,11,15,20,52,86,87). The signaling pathways underlying the converse process, whereby spirochetes transit from the mammalian host into naïve I. scapularis ticks, have received comparatively little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hk2 was widely presumed to be the cognate HK for Rrp2, Xu et al (86) recently demonstrated that the high-energy, phosphoryl donor acetyl phosphate (acetylϳP) is capable of phosphorylating Rrp2 in vitro and, more importantly, that Hk2 is not required for activation of Rrp2 in vivo. Once activated, Rrp2ϳP acts as a transcriptional activator for the alternate sigma factor RpoN (6,87), which in turn controls expression of the spirochete's other alternate sigma factor, RpoS (7,20,36,52,70). Genes within the Rrp2/ RpoN/RpoS regulon promote tick-to-mammal transmission (30) and early murine infection (10,20,32,68,80,83).…”
mentioning
confidence: 99%